Perfis de profissionalização: um contributo sociológico para a compreensão das ONGD portuguesas - Neusa Marcos (2017)
In the scope of the debate on the (in)effectiveness of development aid, this article seeks to discuss the organizational and management models of Non-Governmental Development Organizations (NGDOs) in terms of their higher and lower orientation towards professionalization as an organizational strategy of efficiency and efficacy. In this sense, and based on the data collected from a survey, we present a typology of four profiles of professionalization applied to 23 Portuguese NGDOs intentionally selected, therefore problematizing their organizational and management models towards professionalization.